Assessing System Justification in Czech Population Using the System Justification Scale - Remr, Jiri (European journal of investigation in health, psychology and education, 2023)
System justification (SJ) is an important construct in social psychology that has received considerable attention over the past three decades. At the empirical level, system justification is examined by means of a specially developed System Justification Scale (SJS), which is designed to explain how individuals accept justice, whether they consider a given social order to be fair, how they evaluate the conditions in the country in which they live, how they accept social change, or to what extent they express compliance with established rules. System justification involves not only those who benefit from the existing social order, but also those who are disadvantaged. In their case, system justification mitigates negative perceptions of objective inequalities and asymmetries. Empirical evidence suggests that system justification may also be associated with higher perceived quality of life. The present study translated and validated the SJS, providing complex and detailed information on the psychometric properties of the scale. In addition, the scale's internal consistency, unidimensionality, and construct validity were examined. The conclusions presented are based on the results of exploratory factor analysis, internal consistency assessment, analysis of variance, correlation analysis, and confirmatory factor analysis. Results were obtained from face-to-face survey data collected from a sample of 1419 individuals representing the Czech population aged 18-79 years. Since the SJS showed high internal consistency, adequately discriminated levels of system justification, and had robust psychometric properties, it could be recommended for further use.
Keywords: justice; social inequalities; CFA; equity; validity; psychometrics; system justification; rule compliance